A new taxon of a primitive moth (Insecta: Lepidoptera: Eolepidopterigidae) from the latest Middle Jurassic of northeastern China. (24th November 2015) - Zhang, Wei-Ting; Shih, Chung-Kun; Labandeira, Conrad C.; Ren, Dong
Abstract: A new genus and species, Aclemus patulus n. gen. n. sp., is described based on a new specimen collected from the latest Middle Jurassic Jiulongshan Formation in Inner Mongolia, China. Based on a combination of characters from this fossil, including a homonomous fore- and hindwing, a 3-branched media vein, wings lacking long cilia on their margins; and a cross-vein absent between subcosta and radius, we establish a new genus assigned to the Eolepidopterigidae. In addition, the diagnosis of Longcapitalis excelsus Zhang, Shih, Labandeira and Ren 2013, is emended based on new fossil material.